Correlation of Metered Dose Inhaler Use Technique and Asthma Control Level in Asthma Patients at a Hospital in Bandung, West Java, Indonesia: Hubungan Ketepatan Penggunaan Metered Dose Inhaler dengan Tingkat Kontrol Asma pada Pasien Asma di Salah Satu Rumah Sakit di Bandung, Jawa Barat, Indonesia - Widyastiwi, Widyastiwi; Nurilsyam, Tsania; Roseno, Mohammad; Farida Lhaksmiwati, Inne (Universitas Tadulako, 2021)
Background: Asthma is still a major health problem in global population, including Indonesia. Antiasthma drugs available in various dosage forms, including inhaler. However, several problems related to inhalation route were found due to its unique device form and spesific use technique. One of the major problems related to inhalation route is inappropriate use technique of inhaler device, which could lead to treatment failure. Therapy outcome can be measured through Asthma Control Test (ACT). Objectives: This study was aimed to evaluate correlation between metered dose inhaler (MDI) use technique and asthma control level in patients. Material and Methods: A cross-sectional analytic study was conducted in May - June 2021. Thirty patients who met inclusion criteria were enrolled in this study. Patients’ MDI use technique and asthma control level were evaluated using a valid and standardized questionnaire. Statistics analysis was performed to determine the correlation between MDI use technique and asthma control level. Results: This study showed that most of asthmatic patients were women in older age, with mild asthma severity for more than 10 years. The most prevalent medication used was Fenoterol HBr, followed by salbutamol, and salmeterol/fluticasone combination. Inappropriate MDI use was found in 70,0% patients, with major problem found in patients’ breathing technique before and during MDI use. Asthma control test was performed and showed that 90,0% of asthmatic patients involved in this study have an uncontrolled asthma. Statistical analysis using Pearson product-moment correlation test showed a positive correlation between proper use of MDI and asthma control level (r=0.425, p<0.05). Conclusions: Patient who properly use MDI may have a higher score in asthma control test, thus have a better control of asthma. This study emphasized pharmacist role as patient educator in ensuring appropriate inhaler use in order to achieve therapeutic goals.